Mutrakrichchhra (UTI)-An Ayurvedic Perspective - Sharma, Shruti; Singh, A K (International Research Journal of Ayurveda & Yoga, 2021)
Mutrakrichchhra is one of the most prevalent health concerns in community practice, and it is a wide word that encompasses almost all urinary tract infection (UTI) diseases reported in modern medicine. Mutrakrichchhra’s pratyatma lakshana is "Dukhena mutra pravritti," which means "discomfort during micturition." A urinary tract infection (UTI) is a disorder in which bacteria enter the urinary tract, stay there, and multiply. Other diseases with Mutrakrichchhra as a lakshana include Ashmari, Mutraghata, Mutraja vriddhri, Arsha, and Gulma. This sickness is described in practically all key sources that discuss its prevalence in the ancient world. In Mutrakrichchhra, the prakupit pitta dosha, combined with vata (mostly Apana vayu), enters the Vasti (urinary bladder) and affects the Mutravaha Srotas, causing symptoms such as Daha,Ruja,Basti-gurutva,Shotha,Muhurmutrata,Peet mutrata, and Sarakta mutrata. The aforementioned symptomatology is more similar to LUTI symptoms (i.e. Urethritis and Cystitis). The purpose of this study was to evaluate the mutrakrichchhra literature review according to Ayurveda.